Pemberdayaan Masyarakat Dalam Pemanfaatan Lahan Pekarangan Untuk Mendukung Ketahanan Pangan Melintasi Pandemi Covid-19 - Mohammad Syaiful Pradana; Nisaul Barokati Selirowangi; Dyla Putri Rahmawati (Community: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of this community service is to improve the citizens skills and knowledge by the training and mentoring of organic crop cultivation in bare land to maintain stability of family food security and applying some simple techniques that are easily implemented by the citizens, especially the housewives group. The methods used in this community service are lectures, discussion and demonstrations (practice). Based on the activity results, it can be concluded that the citizens are very enthusiastic and actively participates in this activity. According to the citizens, this activity is very helpful in providing enthusiasm, motivation and knowledge to them in building a healthy and sustainable food security family.